Initial experience with a newly developed antirefluxive ureter stent - Ritter, Manuel; Krombach, Patrick; Michel, Maurice Stephan; Häcker, Axel (Urological research, 2012)
The objective of this study was to assess the functional efficacy of newly developed antirefluxive ureter stents (DJ), by performing immediate post-stenting cystograms on patients with acute ureteral obstruction requiring a DJ stent, and assessing stent-related symptoms by means of ureteral stent symptoms questionnaire (USSQ). Patients with acute hydronephrosis requiring internal drainage were randomized to receive either an antirefluxive DJ or a conventional DJ (7 Fr., 26 cm, polyurethane, Urovision®, Germany). Mean stone size was 6.64 ± 3.33 and 6.5 ± 3.54 mm. Immediately after correct placement of the DJ, 200 ml of diluted contrast media was introduced into the bladder under fluoroscopic control to detect vesicoureteral reflux (VUR). Patients completed German versions of the USSQ on days 2 and 7 following stent placement, and 1 week after stent removal. The results were analyzed. 13 conventional and 16 antirefluxive stents were placed in 29 patients. Reflux was documented in eight conventionally stented patients (62.5%). Two of the 16 patients with antirefluxive stents (22%) presented reflux. 1 week after stent implantation, the mean pain value was 1.1 in the antirefluxive group and 3 in the standard group (p < 0.062). Flank pain during micturition occurred after 2 days in seven patients (58%) with standard stents and in three patients (33%) with antirefluxive stents (p < 0.23). 1 week after stent insertion, flank pain had dropped to 40% in the standard group and 11% in the antirefluxive group (p < 0.3). Our initial experience showed that the antirefluxive system might be effective in terms of reflux prevention and reduction of stent related symptoms especially during sexual intercourse.
Published online: 18 August 2011
Gesehen am 28.06.2018